Optimal control simulation predicts effects of midsole materials on energy cost of running. Issue 8 (11th June 2019) - Dorschky, Eva; Krüger, Daniel; Kurfess, Nicolai; Schlarb, Heiko; Wartzack, Sandro; Eskofier, Bjoern M.; van den Bogert, Antonie J.
Abstract: Testing sports equipment with athletes is costly, time-consuming, hazardous and sometimes impracticable. We propose a method for virtual testing of running shoes and predict how midsoles made of BOOST TM affect energy cost of running. We contribute a visco-elastic contact model and identified model parameters based on load-displacement measurements. We propose a virtual study using optimal control simulation of musculoskeletal models. The predicted reduction in energy cost of ∼ 1 % for BOOST TM in comparison to conventional materials is consistent with experimental studies. This indicates that the proposed method is capable of replacing experimental studies in the future.